Technology Education considering children’s needs: Evidence-based development of Inclusive materials for learning with robots at primary level (The 40th International Pupils’ Attitudes Towards Technology Conference Proceedings 2023, 2023)
The developmental task inclusion effects the design of teaching and learning regarding technology education at primary level. National studies have addressed the issue and have devoted efforts to theory-based development of conditions for inclusive education and their empirical substantiation (Schröer & Tenberge 2022). In German primary schools the subject ‘Sachunterricht’ includes among other domains technology education. An essential field of research is shaping the developmental task inclusion in the context of technology education. However, narrowing down the concept of inclusive education for the multiperspective school subject ‘Sachunterricht’ is complex (Seitz 2018). The use of potentials and consideration of individual needs is one distinguishable context when conceptualizing inclusive education in ‘Sachunterricht’. The consideration of needs in classrooms can be substantiated based on the theory of basic needs (Krapp 2005). Research demonstrates that problemsolving activities with varying degrees of self-direction take different needs into account (Tenberge 2002; Beinbrech 2003). However, the design and substantiation of learning settings, that regard to pupils needs, have so far been largely omitted by research. This justifies the idea of the presented research project. Based on the theory of basic needs, rooted in developmental psychology (Ryan & Deci 2018), a set of problems and tasks for problemsolving with the learning robot Bluebot™ was developed. Learning settings were tested in classrooms and evaluated in a first cycle to adapt them based on evidence. Preliminary findings of pre-post comparisons show effects on problemsolving skills and self-efficacy. The present article falls into four sections of which the first one will define the fundamental concepts addressed. After substantiating the requirements of inclusive technology education, section two will introduce the adaptive set of tasks for technological problemsolving at primary level. Based on the methodical framework in section three, preliminary findings from the first cycle of a design-based-research project are presented and discussed.